A percepção da criança como outrem em Merleau-Ponty - Tiberio, Juliana Gilo (2022)
The research intends to work on the theme of perception, having as a privileged issue the theme of the child as another from the phenomenological perspective of Maurice Merleau-Ponty (1908-1961). Such investigation is conducted from the following question: how does Merleau-Ponty circumscribe the concept of perception within the scope of the childhood phenomenon? In the midst of this questioning point, the general objective is to explain the phenomenon of children's perception in a convergence with the approaches of the psychological sciences of the time, such as Gestalttheorie. Then, it is a matter of describing how the child's relationship with himself and with others takes place, through perception as an initiation into the world. For this, however, we will examine how the philosopher understands the notions of perception and body in order precisely to better situate the horizon of child intersubjectivity, a debate that lacked a wider audience at the time. This, for example, becomes, here, within this thematic scope, the main reason why Merleau-Ponty approaches child psychology and pedagogy, disciplines, in fact, that will become the focus of a more immediate interest in his famous Courses at the Sorbonne from 1949 to 1952. From this perspective, Merleau-Ponty's phenomenological work can be a fertile entry into the subject, given the wealth of descriptions in a critical confrontation, but, at times, also innovative in the field of such discourses. It is mainly a matter of describing how the child's entry into the perceived world opens, questioning, therefore, the need for the child to be perceived as someone who learns, without a doubt, but who also has something to teach the adult, as is able to take its place in the world. From a methodological point of view, the research is supported by important reflections that the philosopher initially exposes, in his first major work, the Phenomenology of Perception (1945) as well as from his courses taught, particularly at the Sorbonne, on the body and the learning of child. In fact, Merleau-Ponty resignifies the very idea of subjectivity through perception, resuming the child's perception, in the classical view, of a behaviorist nature in order to resignify it, through the Gestalt notion, within Psychology the form. Finally, the investigation of this theme seeks to raise the hypothesis of the concept of body schema, in which the child perceives himself, others and the world. After all, it is at the beginning of life that the child begins to use his body schema to perceive others in a way that this perception reveals itself as if it was later than that of his own body.